Bioconversion on Wastewater of Soybeans using Microbial Fuel Cell - Cahyono, Yohanes A; Madurani, Tilana; Azzahra, Widya F; Lestari, Retno A S (Advance Sustainable Science, Engineering and Technology, 2019)
Microbial fuel cell (MFC) is a technology developed to obtain new sources of renewable energy to produce electricity.  It can be an alternative for wastewater treatment and bioenergy producers of renewable electricity. This method requires bacteria to convert substrate in wastewater into electrical energy. The mechanism of MFC were oxidation of substrate by bacteria to produce electrons and protons at the anode. The proton in anode chamber passes through a membrane exchange to the cathode chamber, however the electrons couldn’t through. It caused accumulation of electron in anode chamber and then both of electrode had a potential difference, so electron in anode chamber passed through membrane exchange to cathode chamber. In this study used dual-chambers reactors with each compartment having 8 cm × 10 cm × 10 cm of dimensions and 5 mm of thickness. This study was subjected to evaluate the performance of MFC in soybean washing wastewater treatment with bacteria of EM4 to analyze the potentials production of electricity energy. The focus of this study was to evaluate the effect of time to electricity. MFC system was observed for 40 hours, measurement of voltages and electric currents performed every 4 hours. The results showed that there was potential of electricity production from soybean wastewater treatment by MFC. The maximum electricity reached in soybean wastewater media were voltage 441 mV (at 24 h), the electric currents 170 µA and the power density 51, 35 mW/m2 (at 24 h after acclimatization). Increasing of time effect to decreasing of electricity produced.Keywords: bioenergy, electricity, microbial fuel cell, membrane, wastewater soybean